7-Ketocholesterol Increases Retinal Microglial Migration, Activation, and Angiogenicity: A Potential Pathogenic Mechanism Underlying Age-related Macular Degeneration - Indaram, Maanasa (Sci Rep, 2015)
Age-related macular degeneration (AMD) has been associated with both accumulation of lipid and lipid oxidative products, as well as increased neuroinflammatory changes and microglial activation in the outer retina. However, the relationships between these factors are incompletely understood. 7-Ketocholesterol (7KCh) is a cholesterol oxidation product localized to the outer retina with prominent pro-inflammatory effects. To explore the potential relationship between 7KCh and microglial activation, we localized 7KCh and microglia to the outer retina of aged mice and investigated 7KCh effects on retinal microglia in both in vitro and in vivo systems. We found that retinal microglia demonstrated a prominent chemotropism to 7KCh and readily internalized 7KCh. Sublethal concentrations of 7KCh resulted in microglial activation and polarization to a pro-inflammatory M1 state via NLRP3 inflammasome activation. Microglia exposed to 7KCh reduced expression of neurotrophic growth factors but increased expression of angiogenic factors, transitioning to a more neurotoxic and pro-angiogenic phenotype. Finally, subretinal transplantation of 7KCh-exposed microglia promoted choroidal neovascularization (CNV) relative to control microglia in a Matrigel-CNV model. The interaction of retinal microglia with 7KCh in the aged retina may thus underlie how outer retinal lipid accumulation in intermediate AMD results in neuroinflammation that ultimately drives progression towards advanced AMD.